2009
DOI: 10.1371/journal.pone.0004259
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Deubiquitinating Enzyme Ubp2 and the E3 Ligase Rsp5 Is Required for Transporter/Receptor Sorting in the Multivesicular Body Pathway

Abstract: Protein ubiquitination is essential for many events linked to intracellular protein trafficking. We sought to elucidate the possible involvement of the S. cerevisiae deubiquitinating enzyme Ubp2 in transporter and receptor trafficking after we (this study) and others established that affinity purified Ubp2 interacts stably with the E3 ubiquitin ligase Rsp5 and the (ubiquitin associated) UBA domain containing protein Rup1. UBP2 interacts genetically with RSP5, while Rup1 facilitates the tethering of Ubp2 to Rsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 72 publications
5
41
0
1
Order By: Relevance
“…1E Upper, compare lanes 1 and 2), supporting the idea that Ubp2 can also de-ubiquitylate RNAPII in vivo. As previously reported (24), ubp3 mutant cells also had an increased amount of ubiquitylated RNAPII ( Fig. 1E Upper, lane 3).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…1E Upper, compare lanes 1 and 2), supporting the idea that Ubp2 can also de-ubiquitylate RNAPII in vivo. As previously reported (24), ubp3 mutant cells also had an increased amount of ubiquitylated RNAPII ( Fig. 1E Upper, lane 3).…”
Section: Resultssupporting
confidence: 88%
“…Therefore, it is formally possible that in vivo, Rsp5 normally only adds mono-ubiquitin. Interestingly, however, Rsp5 forms a complex with the ubiquitin protease Ubp2, which has been shown to affect certain other protein ubiquitylation pathways (23,24). We purified TAP-tagged Ubp2 and found that substoichiometric amounts of Rsp5 co-purified, as previously observed by others (23,24).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Yeast (strain S288C) soluble cell-free extract was generated by glass bead beating as described previously (23). 5 mg (500 l of 10 mg/ml protein) of soluble extract was precipitated overnight at Ϫ20°C by the addition of 5 volumes of ice-cold acetone.…”
Section: Methodsmentioning
confidence: 99%